Archeology of the taking-care (Psicologia USP, 2006)
The concept of taking-care, included a long ago in the treatement and then to the concept of therapeutics, returns after little time in the studies, researchs and reflexions in the human sciences, But, from now on, it is emancipated from its medical adherences and connotations due to their excessives reductions. The present article proposes an archeology ( in the Foucault's sense) of the taking-care- from its animal origin to its cultural and historical forms- and put in evidence the subversion produced in the field of taking-care, from practices to speechs, the emergency and domination of the science discourse.